Schiaparelli & the artists - Ades, Dawn 1943-; Albrecht, Donald 1951-; Bergé, Pierre 1930-2017 (Rizzoli, 2017)
"Published on the occasion of the couture house's ninetieth anniversary, this book celebrates Elsa Schiaparelli's shared creative passion with the twentieth century's most esteemed artists. Known for her bravado and boundary-pushing dresses, Elsa Schiaparelli is undoubtedly one of the greatest icons of twentieth-century fashion. After launching her eponymous haute couture house in Paris in 1927, the Roman-born designer captured the attention of the world at large not only thanks to her trompe l'oeil patterns and surrealist forms--but also because of her creative relationships with some of the epoch's most renowned artists. From Salvador Dali, who collaborated with Schiaparelli on her infamous Lobster Dress to Alberto Giacometti's furnishings for her salon and Rene Magritte, whose surrealist works inspired some of the designer's creations, this beautifully illustrated tome delves into the couturiere's fascinating rapports with these artistic legends. Through never-before-seen photography, intimate anecdotes, and essays penned by some of today's most authoritative fashion critics, curators, and personalities, this volume is the first definitive work dedicated to the shared inspiration between the designer and her circle of artist friends. Unique in its breadth of artwork and diverse contributors, this visually stunning book is a must for anyone interested in avant-garde art, twentieth-century fashion, or thought-provoking design."--Provided by publisher
Keywords: Schiaparelli, Elsa -- 1890-1973; Geschichte 1900-1999; Design; Mode; Schiaparelli, Elsa / 1890-1973; Schiaparelli, Elsa / 1890-1973 / Influence; Fashion and art / History / 20th century; Fashion designers / Italy / Biography; Fashion and art; Fashion designers; Influence (Literary, artistic, etc.); Italy; 1900-1999; Biographies; Biography; History; Bildband